Efeito da nutrição na idade à puberdade e desenvolvimento da glândula mamária de cordeiras - Dantas, Ariane [UNESP]; Siqueira, Edson Ramos [UNESP]; Fernandes, Simone [UNESP]; Castilho, André Michel [UNESP]; Santos, Paola Tomotani Rodrigues [UNESP] (My University, 2016)
Nutritional management is one of the main parameters that influence reproduction of animals, reflecting directly on the herd reproductive efficiency. Nutritional imbalance cause impaired reproductive function which is activated again when the demand for maintenance, growth and nutrient reserves are met. Thus, to ensure the beginning of reproductive activity in satisfactory age, it is necessary to supply food enough to provide body developing on lambs. However, despite the high rate of overfeeding promote weight gain in animals and sexual precocity, it can also cause damage to mammary gland development. Therefore, the development of a nutrient management to equalize body, reproductive and breast development in lambs, especially during the growth phase, is critical. Thus, conducting studies in this area is of utmost importance. Therefore, this review aims to describe the influence of nutrition on physiological processes of the onset of puberty and mammary gland development of lambs, seeking greater understanding of this subject.
Effect of nutrition in age at puberty onset and mammary gland development of ewe lambs
Keywords: Mammary tissue; Nutrition; Reproductive activity; Sheep